(untitled) (Journal of Economics and Management Research, 2020)
اوجدت الهندسة المالية الاسلامية اربعة عشر صيغة مختلفة لصكوك الاستثمار. و من خلال تحليلنا لنوع الصكوك المصدرة في السوق المحلية و الدولية بين 2010 الى 2019. وجدنا ان صكوك المرابحة لوحدها تشكل 40% من مجموع الصيغ المصدرة في سوق المال. في حين لم تتعدى صكوك الاستصناع و السلم %1. و قد شكلت صكوك المرابحة، الاجارة و الوكالة الصيغة الاكثر استعمالا في سوق الصكوك، حيث تغطي مجتمعة 75 % من مجموع الصكوك. و هو ما يدل على ان سوق الصكوك لا يعرف تكافؤا في نوعية الصكوك المصدرة و بالتالي فانه لايستفيد بالشكل الامثل من التنوع الذي اوجدته الهندسة المالية الاسلامية. Islamic financial engineering has created fourteen different forms of investment Sukuk. Through this research, we aim to study the diversity of the forms of Sukuk issued in the local and international markets between 2010 and 2019. We found that the Murabaha Sukuk alone account for 40% of the total issued formulas, while the Istisna’a and Salam Sukuk did not exceed 1%. The Murabaha, Ijarah, and Wakala Sukuk were the most used form in the Sukuk market, as they collectively cover 75% of the total Sukuk. This means that the Sukuk market does not have parity in the quality of the issued Sukuk, and therefore it does not benefit optimally from the diversity created by Islamic financial engineering.